Answer and Step-by-step explanation:
y=6x² +2x - 20
let a=6
let b= 2
let c = -20
Using Quadratic Formula by hand Using Factoring and the Zero Property Product Using Completing the Square Using Graphing on the Calculator
using Quadratic Formula
-b ± √( b² - 4ac)
2a
-2 ± √( 2² - 4*6(-20))
2*6
-2 ± √( 2² - 4*6(-20))
2*6
-2 ± √(484)
2*6
20/12 = 5/3
-24/12 = -2
the answers are 5/3 ; -2
use by Factoring
0=6x² +2x - 20
0 =2( 3x² +x - 10)
=2 ( 3x-5) ( x+2)
by using the zero product property
3x-5 = 0
x+2 = 0
3x=5
x =-2
x = 5/3
x = -2
by using completing the square
y=6x² +2x - 20 Add 20
20=6x² +2x Divide by 6
20/6 = x² +2/6x
10/3 = x^2 +1/3x Take the coefficient of x and divide by 2
1/3 /2 = 1/6 Square it
(1/6) ² = 1/36 Add it to both side s
10/3 + 1/36 = x² +1/3x+ 1/36
120/36 + 1/36 = ( x+ 1/6)²
121/ 36= ( x+ 1/6)² Take the square root of both side
√(121/ 36) = √( ( x+ 1/6)²)
±11/6 = x+1/6 Subtract 1/6 from both side
-1/6 ±11/6 = x
-1/6 - 11/6 = x
-1/6 + 11/6 = x
-12/6 =x
10/6 =x
x = -2
x = 5/3
by using a graphing computer